# Simplify and express each of the following in exponential form:$(i)$. $\frac{2^3\times3^4\times4}{3\times32}$$(ii). [(5^2)^{3\ }\times5^4]\div5^7$$(iii)$. $(25^4\div5^3)$$(iv). \frac{3\times7^2\times11^8}{21\times11^3}$$(v)$. $\frac{3^7}{3^4\times3^3}$$(vi). 2^0+3^0+4^0$$(viii)$. $2^0\times3^0\times4^0$$(viii). (3^0+2^0)\times5^0$$(ix)$. $\frac{2^8\times a^5}{4^3\times a3}$$(x). (\frac{a^5}{a^3})\times a^8$$(xi)$. $\frac{4^5\times a^8b^3}{4^5\times a^5b^2}$$(xii)$. $(2^3\times2)^2$

#### Complete Python Prime Pack

9 Courses     2 eBooks

#### Artificial Intelligence & Machine Learning Prime Pack

6 Courses     1 eBooks

#### Java Prime Pack

9 Courses     2 eBooks

Given:

$(i)$. $\frac{2^3\times3^4\times4}{3\times32}$

$(ii)$. $[(5^2)^{3\ }\times5^4]\div5^7$

$(iii)$. $(25^4\div5^3)$

$(iv)$. $\frac{3\times7^2\times11^8}{21\times11^3}$

$(v)$. $\frac{3^7}{3^4\times3^3}$

$(vi)$. $2^0+3^0+4^0$

$(vii)$. $2^0\times3^0\times4^0$

$(viii)$. $(3^0+2^0)\times5^0$

$(ix)$. $\frac{2^8\times a^5}{4^3\times a^3}$

$(x)$. $(\frac{a^5}{a^3})\times a^8$

$(xi)$. $\frac{4^5\times a^8b^3}{4^5\times a^5b^2}$

$(xii)$. $(2^3\times2)^2$

To do: To simplify and express each of the above in exponential form.

Solution:

$(i)$. $\frac{2^3\times3^4\times4}{3\times32}$

$=\frac{2^3\times3^4\times2^2}{3\times2^5}$

$=\frac{2^{3+2}\times3^4}{3\times2^5}$       $[\because\ a^m\times a^n=a^{m+n}]$

$=\frac{2^5\times3^4}{3\times2^5}$

$=2^{5-5}\times 3^{4-1}$

$=2^0\times3^3$                                          $[a^m\div a^n=a^{m-n}]$

$=1\times3^3$                                              $[\because a^0=1]$

$=3^3$

$(ii)$. $[(5^2)^{3\ }\times5^4]\div5^7$

$=(5^6\times5^4)\div5^7$                    $[(a^m)^n=a^{m\times n}]$

$=(5^{6+4})\div5^7$                               $[\because\ a^m\times a^n=a^{m+n}]$

$=5^{10}\div5^7$

$=5^{10-7}$                                              $[a^m\div a^n=a^{m-n}]$

$=5^3$

$(iii)$. $(25^4\div5^3)$

$=(5^2)^4\div5^3$

$=5^8\div5^3$                                        $[(a^m)^n=a^{m\times n}]$

$=5^{8-3}$                                               $[a^m\div a^n=a^{m-n}]$

$=5^5$

$(iv)$. $\frac{3\times7^2\times11^8}{21\times11^3}$

$=\frac{3\times7^2\times11^8}{3\times7\times11^3}$

$=3^{1-1}\times7^{2-1}\times11^{8-3}$             $[a^m\div a^n=a^{m-n}]$

$=3^0\times7^1\times11^5$

$=7\times11^5$

$(v)$. $\frac{3^7}{3^4\times3^3}$

$=\frac{3^7}{3^{4+3}}$                              $[\because\ a^m\times a^n=a^{m+n}]$

$=\frac{3^7}{3^7}$

$=3^{7-7}$                                                $[a^m\div a^n=a^{m-n}]$

$=3^0$

$=1$                                                              $[\because a^0=1]$

$(vi)$. $2^0+3^0+4^0$

$=1+1+1$                                                     $[\because a^0=1]$

$=3$

$(vii)$. $2^0\times3^0\times4^0$

$=1\times1\times1$                                                $[\because a^0=1]$

$=1$

$(viii)$. $(3^0+2^0)\times5^0$

$(1+1)\times1$                                                             $[a^0=1]$

$=2\times1$

$=2$

$(ix)$. $\frac{2^8\times a^5}{4^3\times a^3}$

$\frac{2^8\times a^5}{(2^2)^3\times a^3}$

$=\frac{2^8\times a^5}{2^6\times a^3}$

$=2^{8-2}\times a^{5-3}$                                    $[a^m\div a^n=a^{m-n}]$

$=2^2\times a^2$

$=(2a)^2$

$(x)$. $(\frac{a^5}{a^3})\times a^8$

$=(a^{5-3})\times a^8$                                  $[a^m\div a^n=a^{m-n}]$

$=(a^2)\times a^8$

$=a^{2+8}$                                     $[\because\ a^m\times a^n=a^{m+n}]$

$=a^{10}$

$(xi)$. $\frac{4^5\times a^8b^3}{4^5\times a^5b^2}$

$=4^{5-5}\times a^{8-5}b^{3-2}$                   $[a^m\div a^n=a^{m-n}]$

$=4^0\times a^3\times b^{1}$

$=1\times a^3\times b$                                $[a^0=1]$

$=a^3b$

$(xii)$. $(2^3\times2)^2$

$=(2^{3+1})^2$                                   $[\because\ a^m\times a^n=a^{m+n}]$

$=(2^4)^2$

$=2^{4\times 2}$                            $[(a^m)^n=a^{m\times n}]$

$=2^8$

Updated on 10-Oct-2022 13:38:51